Konovalov - Gorky, Maksim, 1868-1936 (Salt Lake City, UT : Project Gutenberg, 2016)
"Konovalov" by Maksim Gorky is a short story written in 1897. The narrator recalls his time working alongside Konovalov, a talented baker with a restless spirit who cannot maintain a stable life. Despite his skills and good intentions, Konovalov is periodically overcome by an urge to abandon everything for drinking and wandering. Through their friendship, philosophical discussions, and encounters with society's outcasts, the story explores one man's struggle with inner demons and his inability to find peace in ordinary existence. (This is an automatically generated summary.)
Wikipedia page about this book: https://it.wikipedia.org/wiki/Konovalov_(racconto)
Release date is 2016-10-30
Produced by Tapio Riikonen
Keywords: Russian fiction -- Translations into Finnish